Challenges in managing ipsilateral femoral neck and shaft fracture at Mission Hospital - Deeptiman James (Wolters Kluwer Medknow Publications, 2016)
Rarity of ipsilateral femoral neck and shaft fracture qualifies it as a difficult fracture to diagnose as well as treat. No ideal treatment option has been defined, and no ideal implant has been assigned for the management of such fractures. Fixation of ipsilateral fractures of femoral neck and shaft are technically demanding. They are also associated with complications such as osteonecrosis of femoral head, delayed union, varus malunion, and nonunion. Treating such complicated fractures in a level V trauma center such as rural mission hospital with limited resources multiplies the difficulty of managing such fracture. This case report highlights the outcome and challenges in treating a patient with ipsilateral femoral neck and shaft fracture in a mission hospital in rural central India.